OUR EXPERIENCE IN THE REHABILITATION OF PATIENTS WITH THE FACIAL NERVE NEUROPАTHY USING THE METHODS OF PHYSIOTHERAPY - Vereshchakina, V.V. (World of Medicine and Biology, 2017)
In this article we present a review of a scientific literature and own observations of physiotherapeutic treatment of patients with the facial nerve neuropathy based on 20-years experience. The effectiveness of the facial nerve paralysis treatment with different methods of physiotherapy has been assessed in our research. Including physiotherapy in the complex treatment significantly increases the efficiency and reduces the treatment time.